2016
DOI: 10.1016/j.jcat.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Lewis acid/Brønsted acid-catalyzed conversion of carbohydrates to 5-hydroxymethylfurfural using zeolite beta

Abstract: We conduct a combined experimental and computational study to reveal the kinetics of tandem glucose isomerization and fructose dehydration to 5-hydroxymethylfurfural (HMF) over a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(96 citation statements)
references
References 58 publications
4
91
1
Order By: Relevance
“…Previous studies [8][9][10] have indicated that B/L had an effect on HMF selectivity,t hus, B/L with variousL */L wasc alculated, and the correlation is presented in Figure 4b.A tasimilarL */L ratio, the HMF selectivity versusB /L exhibitedavolcano-type curve, which indicates that there is ab alance of Lewisa nd Brønsted acids for the glucose isomerization to fructosea nd fructose dehydration to HMF,a nd not that ah igher B/L corresponds to ab etter selectivity to HMF.M oreover,t his surprising result was not only consistent with the studies reportedb yO rdomsky et al, [8,13] in which al ow B/L (ca. 0.09-0.27) promoted the formationo fH MF from glucosea nd inhibited the formation of humins, but also in agreement with the study of Zhang et al, [10] in which ah igh B/L (ca.…”
Section: Effect Of the Acidity On The Selectivity To Hmfla And Huminsmentioning
confidence: 78%
See 2 more Smart Citations
“…Previous studies [8][9][10] have indicated that B/L had an effect on HMF selectivity,t hus, B/L with variousL */L wasc alculated, and the correlation is presented in Figure 4b.A tasimilarL */L ratio, the HMF selectivity versusB /L exhibitedavolcano-type curve, which indicates that there is ab alance of Lewisa nd Brønsted acids for the glucose isomerization to fructosea nd fructose dehydration to HMF,a nd not that ah igher B/L corresponds to ab etter selectivity to HMF.M oreover,t his surprising result was not only consistent with the studies reportedb yO rdomsky et al, [8,13] in which al ow B/L (ca. 0.09-0.27) promoted the formationo fH MF from glucosea nd inhibited the formation of humins, but also in agreement with the study of Zhang et al, [10] in which ah igh B/L (ca.…”
Section: Effect Of the Acidity On The Selectivity To Hmfla And Huminsmentioning
confidence: 78%
“…Ar ecent study showed that the HMF formation rate exhibitedavolcano-type curve versusB /L, and the maximum HMF yield approached 60 %i nb iphasic conditions. [9] These reports indicated that the Lewis acid sites played important role in the isomerization of glucose, and the HMF selectivity was correlated to B/L. However,t ot he best of our knowledge,n o clear correlation between the strengtha nd type of acid sites and product selectivity has ever been reported.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…23,74,108 H-Beta is not an efficient catalyst for HMF production from glucose, even though it is bifunctional. 154 Similarly, HMF yield is higher using the bifunctional PVP-SO 3 H-SBA-15 than a combination of PVP in solution and SO 3 H-SBA-15. 117 Bifunctional catalysts containing redox and acid functionalities (usually metal nanoparticles supported in metal oxides) also have important application in the conversion of biomass-derived saccharides.…”
Section: Catalysts: Towards Heterogeneous Catalysis Bifunctional Catmentioning
confidence: 96%
“…[1][2][3][4][5] Among various processes explored for biomass transformation, dehydration of carbohydrates, an important type of biomass, to produce 5-hydroxymethylfurfural (HMF) is one of the most successful routes. [6][7][8][9] As one of the top building block compounds obtained from biomass, 10 HMF can be transformed into many kinds of value-added compounds and materials, [11][12][13][14] which are currently produced mainly from petroleum.…”
Section: Introductionmentioning
confidence: 99%